2011
DOI: 10.4999/uhod.09061
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cervical Cancer: Results from a Hospital-Based Case-Control Study

Abstract: The aim of this study was to investigate risk factors for cervical cancer in Turkish women. In a hospital-based case-control study in ‹stanbul, 209 patients with histologically confirmed cervical cancer were compared with 1050 controls, who were admitted to the different departments of the same hospital. Odds ratios (OR) and 95% confidence intervals (CI) were obtained from multivariate logistic regression analysis, fitted by the method of maximum likelihood. Risk factors for cervical cancer were found to be ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
(30 reference statements)
3
19
1
5
Order By: Relevance
“…They suggested that low education level is related with an increase of sexual activity on young age, numerous sexual partners and bad genital hygiene. 27 Statistically in this research there is no significant correlation between smoking history and cervical carcinoma. This result is different with meta-analysis about correlation between smoking and cervical carcinoma by Gandini et all.…”
Section: Resultsmentioning
confidence: 50%
“…They suggested that low education level is related with an increase of sexual activity on young age, numerous sexual partners and bad genital hygiene. 27 Statistically in this research there is no significant correlation between smoking history and cervical carcinoma. This result is different with meta-analysis about correlation between smoking and cervical carcinoma by Gandini et all.…”
Section: Resultsmentioning
confidence: 50%
“…10 Seseorang dengan tingkat pendidikan rendah cenderung untuk menikah dini sehingga hubungan seksual pertama kali terjadi pada usia muda. 11 Berdasarkan penelitian Reis et al (2011), ditemukan bahwa hubungan seksual pertama yang terjadi pada usia yang terlalu muda merupakan faktor risiko terjadinya kanker serviks. 8 Lebih dari 81% penderita kanker serviks pada penelitian ini merupakan ibu rumah tangga dan tidak bekerja, sejalan dengan hasil penelitian yang dilakukan Chandrawati (2016) bahwa pekerjaan merupakan faktor risiko terjadinya kanker serviks.…”
Section: Metodeunclassified
“…11 Berdasarkan penelitian Reis et al (2011), ditemukan bahwa hubungan seksual pertama yang terjadi pada usia yang terlalu muda merupakan faktor risiko terjadinya kanker serviks. 8 Lebih dari 81% penderita kanker serviks pada penelitian ini merupakan ibu rumah tangga dan tidak bekerja, sejalan dengan hasil penelitian yang dilakukan Chandrawati (2016) bahwa pekerjaan merupakan faktor risiko terjadinya kanker serviks. 12 Hal ini kemungkinan disebabkan wanita yang tidak bekerja kurang mendapatkan akses terhadap informasi tentang kanker serviks, baik tentang hygiene vagina, tanda/gejala awal maupun terapinya.…”
Section: Metodeunclassified
“…Age did intercourse less than 20 years old have a risk three times more likely to have precancerous lesions of the cervix. 23 The increased risk of precancerous lesions of the cervix is not only influenced by the age of first sexual intercourse but is also affected by the age at first marriage, the social economy and the level of a person's knowledge.…”
Section: The Age Of First Intercourse Relationship With the Incidencementioning
confidence: 99%